A Novel Structure of a Wideband Zero-Bias Power Limiter for ISM Band - Khalifa Echchakhaoui; Elhassane Abdelmounim; Jamal Zbitou; Hamid Bennis; Ahmed Errkik; Angel Mediavilla Sanchez (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this paper, a new broadband microwave microstrip power limiter is designed and realized. The Power Limiter is based on microstrip technology integrating a Zero Bias commercial Schottky diodes HSMS2820.The power limiter is optimized and validated in two steps. The enhanced and achieved circuit is obtained by concatenating two basic structures. The final circuit was validated into simulation by using ADS solver. Finally this circuit was realized and tested. Simulation and measurement results are in a good agreement. The final circuit achieves a limiting rate of 14 dB with a threshold input power level of 0 dBm until a maximum input power level of 30 dBm.